Simulation of fire exposure behavior to building structural elements using LISA FEA V.8. - Aco Wahyudi Efendi (International Journal of Advanced Science and Computer Applications, 2023)
The purpose of this work is to evaluate the most generally used techniques for measuring the thermal conductivity of concrete, as well as to consider the variables influencing the thermal conductivity of cement-based materials. Based on previous research indicating that the pattern of heat flow can be modeled in a numerical analysis program and provide a hue of coverage and differences in indoor temperature conditions, as well as the impact that occurs on several elements in the room, a heat simulation analysis was performed in this study due to a fire. The researchers in this study simulated the flow pattern from the temperature that occurred due to fire in a room measuring 4000x4000 mm with a wall thickness of 200 mm with Hebel/light brick material, floor plate thickness was 120 mm, and the size of the building column structural elements was 400x400 mm with the material reinforced concrete. According to the simulation results of a fire that occurred in the middle of the room with two conditions for installing hebel walls, namely covering the building structure columns and those behind the building structure columns, there is an increase in the temperature of the column with a ratio of 1.062 in the two conditions where the temperature of the wall lining the column is 6.28% lower than the temperature of the wall behind the column, while the heat flux magnitude that occurs is lower.